TiCl4 Pretreatment and Electrodeposition Time Investigations of ZnO Photoelectrodes Preparation for Dye Sensitized Solar Cells - Xiaoping Zou; Yan Liu; Cuiliu Wei; Zongbo Huang; Xiangmin Meng (International Journal of Photoenergy)
TiCl4 pretreatment is used in the fabrication of high performance photoanodes for dyes-sensitized solar cells (DSSCs). In this paper, TiCl4 pretreatment was used on fluorine doped tin oxide (FTO) before fabricating ZnO films by electrochemical method. The effects of TiCl4 pretreatment on some important parameters of solar cells, such as short-circuit current (Jsc) and filling factor, were investigated. The morphology of ZnO films was changed after TiCl4 pretreatment, which can offer large surface area to absorb much more dyes. When the time of electrodeposition was 3 min, the dyes-sensitized solar cells (DSSCs) based on TiCl4 pretreatment ZnO films showed more superior photoelectrochemical performance. The parameters of DSSCs are greatly improved. The DSSC based on ZnO films after TiCl4 pretreatment has a very promising value for fabricating high performance solar cells.